Mentors that Matter: International Student Leadership Development and Mentor Roles - Shalka, Tricia R; Corcoran, Chloe S; Magee, Brian T (Journal of International Students, 2019)
Leadership development has been identified as an important outcome of higher education in the United States. However, relatively few scholars have investigated leadership development outcomes of international students studying in U.S. postsecondary contexts. Using data from the Multi-Institutional Study of Leadership, the purpose of this quantitative study was to investigate the role of mentors in fostering leadership development outcomes for international students. Results suggest that international students whose primary college mentor is a faculty member or a student affairs professional demonstrate higher levels of both socially responsible leadership capacity and leadership self-efficacy than those international students who identify their most significant mentor as another student.